Synergistic Interaction of Low Salinity Stress With Vibrio Infection Causes Mass Mortalities in the Oyster by Inducing Host Microflora Imbalance and Immune Dysregulation - Li, Xin; Yang, Ben; Shi, Chenyu; Wang, Hebing; Yu, Ruihai; Li, Qi; Liu, Shikai (Frontiers in Immunology, 2022)
A sudden drop in salinity following extreme precipitation events usually causes mass mortality of oysters exposed to pathogens in ocean environment. While how low salinity stress interacts with pathogens to cause mass mortality remains obscure. In this study, we performed an experiment by low salinity stress and pathogen infection with Vibrio alginolyticus to investigate their synergistic effect on the mortality of oysters toward understanding of the interaction among environment, host, and pathogen. We showed that low salinity stress did not significantly affect proliferation and virulence of V. alginolyticus, but significantly altered microbial composition and immune response of infected oysters. Microbial community profiling by 16S rRNA amplicon sequencing revealed disrupted homeostasis of digestive bacterial microbiota with the abundance of several pathogenic bacteria being increased, which may affect the pathogenesis in infected oysters. Transcriptome profiling of infected oysters revealed that a large number of genes associated with apoptosis and inflammation were significantly upregulated under low salinity, suggesting that low salinity stress may have triggered immune dysregulation in infected oysters. Our results suggest that host-pathogen interactions are strongly affected by low salinity stress, which is of great significance for assessing future environmental risk of pathogenic diseases, decoding the interaction among environment, host genetics and commensal microbes, and disease surveillance in the oyster.